21+3c-7(2-3c)=4(c-5)3c+27

Simple and best practice solution for 21+3c-7(2-3c)=4(c-5)3c+27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 21+3c-7(2-3c)=4(c-5)3c+27 equation:


Simplifying
21 + 3c + -7(2 + -3c) = 4(c + -5) * 3c + 27
21 + 3c + (2 * -7 + -3c * -7) = 4(c + -5) * 3c + 27
21 + 3c + (-14 + 21c) = 4(c + -5) * 3c + 27

Reorder the terms:
21 + -14 + 3c + 21c = 4(c + -5) * 3c + 27

Combine like terms: 21 + -14 = 7
7 + 3c + 21c = 4(c + -5) * 3c + 27

Combine like terms: 3c + 21c = 24c
7 + 24c = 4(c + -5) * 3c + 27

Reorder the terms:
7 + 24c = 4(-5 + c) * 3c + 27

Reorder the terms for easier multiplication:
7 + 24c = 4 * 3c(-5 + c) + 27

Multiply 4 * 3
7 + 24c = 12c(-5 + c) + 27
7 + 24c = (-5 * 12c + c * 12c) + 27
7 + 24c = (-60c + 12c2) + 27

Reorder the terms:
7 + 24c = 27 + -60c + 12c2

Solving
7 + 24c = 27 + -60c + 12c2

Solving for variable 'c'.

Reorder the terms:
7 + -27 + 24c + 60c + -12c2 = 27 + -60c + 12c2 + -27 + 60c + -12c2

Combine like terms: 7 + -27 = -20
-20 + 24c + 60c + -12c2 = 27 + -60c + 12c2 + -27 + 60c + -12c2

Combine like terms: 24c + 60c = 84c
-20 + 84c + -12c2 = 27 + -60c + 12c2 + -27 + 60c + -12c2

Reorder the terms:
-20 + 84c + -12c2 = 27 + -27 + -60c + 60c + 12c2 + -12c2

Combine like terms: 27 + -27 = 0
-20 + 84c + -12c2 = 0 + -60c + 60c + 12c2 + -12c2
-20 + 84c + -12c2 = -60c + 60c + 12c2 + -12c2

Combine like terms: -60c + 60c = 0
-20 + 84c + -12c2 = 0 + 12c2 + -12c2
-20 + 84c + -12c2 = 12c2 + -12c2

Combine like terms: 12c2 + -12c2 = 0
-20 + 84c + -12c2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-5 + 21c + -3c2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-5 + 21c + -3c2)' equal to zero and attempt to solve: Simplifying -5 + 21c + -3c2 = 0 Solving -5 + 21c + -3c2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. 1.666666667 + -7c + c2 = 0 Move the constant term to the right: Add '-1.666666667' to each side of the equation. 1.666666667 + -7c + -1.666666667 + c2 = 0 + -1.666666667 Reorder the terms: 1.666666667 + -1.666666667 + -7c + c2 = 0 + -1.666666667 Combine like terms: 1.666666667 + -1.666666667 = 0.000000000 0.000000000 + -7c + c2 = 0 + -1.666666667 -7c + c2 = 0 + -1.666666667 Combine like terms: 0 + -1.666666667 = -1.666666667 -7c + c2 = -1.666666667 The c term is -7c. Take half its coefficient (-3.5). Square it (12.25) and add it to both sides. Add '12.25' to each side of the equation. -7c + 12.25 + c2 = -1.666666667 + 12.25 Reorder the terms: 12.25 + -7c + c2 = -1.666666667 + 12.25 Combine like terms: -1.666666667 + 12.25 = 10.583333333 12.25 + -7c + c2 = 10.583333333 Factor a perfect square on the left side: (c + -3.5)(c + -3.5) = 10.583333333 Calculate the square root of the right side: 3.253203549 Break this problem into two subproblems by setting (c + -3.5) equal to 3.253203549 and -3.253203549.

Subproblem 1

c + -3.5 = 3.253203549 Simplifying c + -3.5 = 3.253203549 Reorder the terms: -3.5 + c = 3.253203549 Solving -3.5 + c = 3.253203549 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + c = 3.253203549 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + c = 3.253203549 + 3.5 c = 3.253203549 + 3.5 Combine like terms: 3.253203549 + 3.5 = 6.753203549 c = 6.753203549 Simplifying c = 6.753203549

Subproblem 2

c + -3.5 = -3.253203549 Simplifying c + -3.5 = -3.253203549 Reorder the terms: -3.5 + c = -3.253203549 Solving -3.5 + c = -3.253203549 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3.5' to each side of the equation. -3.5 + 3.5 + c = -3.253203549 + 3.5 Combine like terms: -3.5 + 3.5 = 0.0 0.0 + c = -3.253203549 + 3.5 c = -3.253203549 + 3.5 Combine like terms: -3.253203549 + 3.5 = 0.246796451 c = 0.246796451 Simplifying c = 0.246796451

Solution

The solution to the problem is based on the solutions from the subproblems. c = {6.753203549, 0.246796451}

Solution

c = {6.753203549, 0.246796451}

See similar equations:

| (8x^3)-(14y)+(12x)=0 | | 1/14b=-2.39 | | 0.37=ln(-2.5k) | | -0.994=ln(-2.5k) | | lnx=2.25 | | 6cos^2x-17cosx+7=0 | | 9=1/2a | | -3x^2+14x+49=-42 | | 2e^5x=14 | | -3x^2+14x+49=42 | | 6.1=x+(-7.3) | | 6cos^2x-17x+7=0 | | 7(x+7)=-11-3x | | -6(1-8k)=-20 | | 5-(-7*-4)=-33 | | 3y=7x-1 | | -28=12+2z | | (2-x).5=10 | | ln(1+x)-lnx=.25 | | -5x-10=5x | | 4(6x+7)=-40+7x | | 6x+15=9x+13-5x | | 16+4r=8(2+7r) | | 8y+6=3x | | 16x^2+3x+1=0 | | x+(x+1)=380 | | 8-6x-x^2=6+x | | -3h-5=-3h | | 9z-5-4z=5z | | 4(-6+p)=0 | | seag(X)=-4.2 | | -5(2-x)=5 |

Equations solver categories